Effect of skill-based educational training for ambulance personnel on neonatal transport for newborn care in coastal South India – a single arm intervention study [version 2; peer review: 1 approved, 2 approved with reservations] - Shantharam Baliga B; Harsha Lashkari P; Sowmini Padmanabh Kamath; Leslie Lewis; Subhodh Shetty S; Santosh Kalyan; Ramesh Holla; Suchitra Shenoy M (F1000Research)
Background Quality of neonatal transport services may impact outcomes. We assessed the effect of skill-based education of ambulance personnel (AP) on outcomes of transported neonates. Methods We conducted a single-arm intervention study (pre and post) over 18 months. We assessed the perceptions and practices of AP on neonatal transport along with ambulance equipment availability/usage. We compared neonatal clinical vital parameters at arrival and clinical outcomes from Neonatal Intensive Care Unit (NICU) pre versus post intervention. We analysed data using SPSS version 25. Results Of 77 AP receiving education, there was significant (p < 0.001) improvement in the perceptions/practices towards temperature regulation (44.55 ± 23.94 vs. 25.94 ± 21.36), glucose homeostasis (46.27 ± 18.83 vs. 18.60 ± 17.50), maintaining asepsis (67.05 ± 17.53 vs. 39.35 ± 16.85), supporting airway (47.73 ± 25.39), circulation (85.26 ± 23.27 vs. 48.45 ± 25.10), along with ambulance equipment availability/usage postintervention. Of 53 neonates studied post intervention, there was a significant reduction in hypothermia (17% vs. 48.4%, p < 0.001), hypoglycemia (16.9% vs. 38.7%, p=0.010), and prolonged capillary refill time (71.7% vs. 46.8%, p=0.042), improvement in the use of intravenous fluids (69.8% vs. 29%, p <0.001), a reduction in growth from umbilical swabs (15.1% vs. 42%, p=0.002) and duration of NICU stay (p = 0.001). Conclusions After educational intervention there was significant improvement in the perceptions and practices of ‘108’ ambulance personnel towards transporting neonates and a significant decrease in hypothermia, hypoglycemia, and duration of NICU stay with improvement in maintenance of circulation and asepsis in neonates.